Profiling the injuries of law enforcement recruits during academy training: a retrospective cohort study - Danny J. Maupin; Elisa F. D. Canetti; Ben Schram; Robert G. Lockie; J. Jay Dawes; Joseph M. Dulla; Rob M. Orr (BMC, 2022)
Abstract Background Injuries within law enforcement are a significant issue as they increase organisational costs and workforce strain. As one of the biggest risk factors of future injury is previous injury, minimising injuries suffered during academy has multiple beneficial and long-term effects, including a healthier and fitter police force. The purpose of this study was to profile the injuries sustained at a law enforcement academy to inform future injury mitigation strategies. Methods Injury data were provided retrospectively (from May 2012 to September 2019) from the official insurance records of a law enforcement academy and included nature, location, and activity performed at time of injury. A total of 4340 (3288 males, 938 females, 114 sex not stated) recruits participated in academy training during this period. Inclusion criteria for the data were (a) injury record related to a recruit, and (b) the recruit was injured during academy training., with injury defined as tissue damage caused by acute or repetitive trauma, inclusive of musculoskeletal, neural, and/or integumentary systems but excluding general medical conditions such as cardiac (e.g. heart attacks) or respiratory (asthma) that was subsequently reported for worker's compensation. Injury incidence rates and proportions were calculated and a Spearman's correlation analysis was conducted between injury rates over successive classes. Results An injury incidence rate of 368.63 injuries per 1000 recruits per year was calculated in this population, with a moderate correlation coefficient (rs = 0.60) of increasing injury rates over chronologically occurring classes. Females also had higher injury rates than male recruits, even across various fitness levels. Trauma to joints and ligaments (49.30%) was the most common injury, and the knee the most common location (23.17%) of injury. Physical training (56.10%) was the most common activity being performed at the time of injury. Conclusions This research demonstrates a large number of lower limb, musculoskeletal injuries that often occur during physical training. Further research is needed to assess suitable injury mitigation programs.